KAJIAN PERAN SUSU SKIM DAN BAKTERI ASAM LAKTAT PADA MINUMAN SINBIOTIK UMBI BENGKUANG (pachyrrhizus erosus) - Mulyani, Tri; HP, Sudaryati; Susanto, Agus (REKAPANGAN, 2011)
Sinbiotik  (eubotic)  is  a  combination  of  prebiotics  and  probiotics.  The  advantage  of  this combination is to enhance  the growth  of  probiotic  bacteria  by prebiotic  substrates. In general, the  raw  material  of  sinbiotik  beverage  is  milk.  At  this  time,  as  product  innovations  made  brew filtrate  sinbiotik  of  yam  tubers  (Pachyrrizus  erosus).  The  advantages  of  this  product  is  the availability of two components as well as the  inulin derived from the  tubers of  yam which acts as a prebiotic and Lactobacillus Casei that act as probiotics. The purpose of this study was to determine the effect of the addition of skim milk and the concentration of starter (Lactobacillus casei)  that  most  optimally  in  the  process  of  making  drinks  sinbiotik  yam  tubers.  The  results showed  that  the  best  treatment  there  is  the  additional  treatment  of  skim  milk  20%  and  the concentration of starter (Lactobacillus Casei) 2%. The results showed total lactic acid bacteria 11.2933 log CFU / ml, 0.5119% total acid, pH 3.7, total dissolved solids 36.0680 (oBrix), inulin content of 3.2503% and 0.3667% soluble protein.Keywords: sinbiotik, skim milk, probiotic bacteria, prebiotic substrates